A density functional theory study of [(4-aminophenyl)imino]methyl-6-methoxy-4-nitrophenol complexes with Co, Ni, Cu and Zn metals - Fellah, Mehmet Ferdi; Bakirdere, Emine Gulhan; Canpolat, Erdal; Kaya, Mehmet (Scientific Publ-India, 2014)
The optimization and IR spectra of the [(4-aminophenyl)imino]methyl-6-methoxy-4-nitrophenol and its complexes with Co, Ni, Cu and Zn metals were determined by means of density functional theory (DFT) calculations using B3LYP formalism. The optimized geometries of complexes have tetrahedral structures. The C=N, C-O and N-H stretching frequency values were calculated to be in good agreement with experimental frequency data for ligand and its complexes with metals. All calculated frequencies are within 1.1% of the regions of experimental frequencies.
Keywords: DFT; Schiff base; transition metal complex